1993
DOI: 10.1111/j.1749-7345.1993.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Soybean Protein for Fish Protein in Formulated Diets for Red Swamp Crawfish Procambarus clarkii1

Abstract: A 10 week laboratory growth trial was conducted with red swamp crawfish Procambarus clarkii to determine the amount of soybean protein that could be substituted for fish protein in formulated crawfish diets without reducing growth. Crawfish received 32% crude protein, isocaloric diets in which protein was supplied by soybean (soy) meal, menhaden fish meal or an isonitrogenous mixture of soybean and fish meal calculated to provide graded levels of each protein source. Dietary protein was provided as: 1) 100% so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
(4 reference statements)
3
21
0
Order By: Relevance
“…It is also apparent that diets containing 15% protein produce suboptimal growth irrespective of the relative inclusion levels of fish meal and soybean meal and are clearly nutritionally deficient. The apparent protein requirement of the yabby falls within the 25-35% range reported for other freshwater crayfish (D'Abramo and Robinson, 1989;New, 1990;Reigh et al, 1993). Furthermore, about 15-20% of the diet (as dry weight) should be composed of animal-based protein ingredients and is consistent with the recommendations made by others (D'Abramo and Robinson, 1989;Reigh et al, 1993).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It is also apparent that diets containing 15% protein produce suboptimal growth irrespective of the relative inclusion levels of fish meal and soybean meal and are clearly nutritionally deficient. The apparent protein requirement of the yabby falls within the 25-35% range reported for other freshwater crayfish (D'Abramo and Robinson, 1989;New, 1990;Reigh et al, 1993). Furthermore, about 15-20% of the diet (as dry weight) should be composed of animal-based protein ingredients and is consistent with the recommendations made by others (D'Abramo and Robinson, 1989;Reigh et al, 1993).…”
Section: Discussionsupporting
confidence: 85%
“…The apparent protein requirement of the yabby falls within the 25-35% range reported for other freshwater crayfish (D'Abramo and Robinson, 1989;New, 1990;Reigh et al, 1993). Furthermore, about 15-20% of the diet (as dry weight) should be composed of animal-based protein ingredients and is consistent with the recommendations made by others (D'Abramo and Robinson, 1989;Reigh et al, 1993). Finally, more than 12% of the total dietary protein should be derived from fish meal, particularly in practical feeds that have a low protein content.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, the source and quality of the soya bean meal should be taken into consideration when a formulated diet is elaborated. PiedadPascual et al (1990), Tidwell et al (1993 and Reigh et al (1993) reported the ability to utilize soya bean meal as dietary protein supplement for some crustaceans, but in those cases, growth performance was not improved in comparison with fish meal diets, possibly due to the presence of active antimetabolites in soya bean that had been incompletely heat-processed (García-Ulloa, 1998), trypsin inhibitors (Ayet et al, 1996), or the amino acid deficiencies in soya bean (Reed and D'Abramo, 1989). The mean SGR in the present study ranged from 1.82 ± 0.67% BW/d for the diet 3 (40%), to 2.62 ± 0.78 for the diet 6 (100%) respectively, being similar to those observed by Jones (1988), and Meade and Watts (1995) for crayfish juveniles fed formulated diet, but lower than that obtained by for Cherax quadricarinatus juveniles, including various soya bean meal levels in the diet.…”
Section: Mean Body Length (Cm)mentioning
confidence: 99%